2021
DOI: 10.3390/ph14100956
|View full text |Cite
|
Sign up to set email alerts
|

Production and Purification of Two Bioactive Antimicrobial Peptides Using a Two-Step Approach Involving an Elastin-Like Fusion Tag

Abstract: Antimicrobial resistance is an increasing global threat, demanding new therapeutic biomolecules against multidrug-resistant bacteria. Antimicrobial peptides (AMPs) are promising candidates for a new generation of antibiotics, but their potential application is still in its infancy, mostly due to limitations associated with large-scale production. The use of recombinant DNA technology for the production of AMPs fused with polymer tags presents the advantage of high-yield production and cost-efficient purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…In recombinant peptide production, a modified peptide encoded by recombinant DNA is cloned in a foreign expression system. Recombinant production gives more control over the peptide sequence, higher yields, and is a more sustainable source of the peptides [ 78 ]. However, this technique requires initial work on proper plasmid construction and genetic design.…”
Section: Peptides and Antiviral Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…In recombinant peptide production, a modified peptide encoded by recombinant DNA is cloned in a foreign expression system. Recombinant production gives more control over the peptide sequence, higher yields, and is a more sustainable source of the peptides [ 78 ]. However, this technique requires initial work on proper plasmid construction and genetic design.…”
Section: Peptides and Antiviral Activitymentioning
confidence: 99%
“…These materials contained antimicrobial peptide sequences. They also concluded that the antimicrobial efficacy of these novel materials is attributable to the peptide sequence, not to the backbone polymer structure [ 78 ]. De Costa et al developed a new fusion material, BMAP-18-A200,based film [ 153 ].…”
Section: Antiviral Peptides As a Surface Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, ELP was used as the purification tag as in the previous examples. However, in this case, after the chemical cleavage and the ITC purification, a chromatographic step was required to improve the recovery of the AMPs (Pereira et al, 2021). This approach showed a yield about 2‐times higher for the Moricin CM4, relative to that obtained with the ELP‐intein‐AMP fusion setup (Table 1, #2 and Figure 2a).…”
Section: Elp Sequences Employed As Fusion Partnersmentioning
confidence: 99%
“…[ 20 ] Due to its low hemolytic and cytotoxic activities, several biotechnological applications have been used to obtain efficient and cost‐effective approaches for the recombinant production and purification of this peptide. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%